Impact of Coronavirus Disease-2019 on Influenza and Tdap Vaccination Rates in Pregnant Patients - Njagu, Ravyn; Freedy, Katherine; Brucker, Amanda; Feng, Kelvin; Lunn, Siera; Greene, Melissa; Swamy, Geeta K.; Dotters-Katz, Sarah (American Journal of Perinatology, 2025)
Influenza and tetanus toxoid reduced diphtheria toxoid, and acellular pertussis (Tdap) are safe and effective vaccines that are recommended in pregnancy. Despite this, significant vaccine hesitancy exists in pregnancy. However, impact of the coronavirus disease 2019 (COVID-19) pandemic on vaccine hesitancy is not well understood. Thus, we sought to describe impact of the COVID-19 pandemic on influenza and Tdap vaccination rates in pregnant patients.Retrospective cohort study of patients delivering at single academic center from October 1, 2017 to August 31, 2021. Patients with missing vaccine data or delivering before 28 weeks (Tdap range) excluded. Patients delivering pre-COVID (October 1, 2017–August 31, 2019) compared with those delivering mid-COVID (October 1, 2020–August 31, 2021). Primary outcomes were vaccination rates for Tdap and influenza. Secondary outcome was rate of dual vaccination (receiving both) and variation by race/ethnicity. Chi-square tests and logistic regression were used to test for changes in vaccination rates.Of 8,650 unique patient pregnancies, 5,925(68.5%) occurred pre-COVID. Median patient age (30 years) and gestational age at delivery (39 weeks) not clinically different between groups. Patients in mid-COVID group had lower numbers of government-assisted insurance (47.3%) and higher non-Hispanic Black compared with pre-COVID (31.5%). The rate of influenza vaccination decreased 8.2 percentage points from pre-COVID to mid-COVID (69.9 vs. 61.7%, p < 0.001). Tdap vaccination rates also decreased, although less-so (88.5 vs. 85.1%, p < 0.001). The rate of patients receiving both vaccines during pregnancy decreased from 66.0 to 58.4% (p < 0.001). Significant decreases in influenza vaccination rates mid-COVID versus pre-COVID was seen in all race–ethnicity groups except non-Hispanic White patients. For Tdap vaccinations, the effect of COVID on the odds of receiving Tdap did not differ across race–ethnicity groups.Rates of influenza, Tdap, and dual vaccination in pregnancy dropped significantly during the COVID-19 pandemic. For influenza, these were most pronounced in all race–ethnicities included with exception of non-Hispanic White. These data emphasize the importance of continued counseling and education on vaccinations in pregnancy and raise important questions regarding vaccine access and patient hesitancy during pandemic-mediated prenatal care.
Keywords: vaccination; influenza; Tdap; COVID-19